2010
DOI: 10.1080/00036840801964708
|View full text |Cite
|
Sign up to set email alerts
|

Rent-sharing and collective wage contracts–evidence from German establishment-level data

Abstract: Using German establishment-level data, this paper analyses whether wages respond to firm-specific profitability conditions. Particular emphasis is given to the question of whether the extent of rent-sharing varies with collective bargaining coverage. In this context, two conflicting hypotheses are tested. The first one asserts that unions exploit their bargaining power at the firmlevel and appropriate a larger share of rents than the bargaining parties in uncovered firms. The second one states that unions favo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 30 publications
(30 reference statements)
0
26
1
Order By: Relevance
“…In my own recent work, I use data from the IAB Establishment Panel and find wages to be positively related to establishment profits. However, this appears to be true only for uncovered establishments, since I fail to detect any positive relationship between wages and local profitability conditions in plants that are subject to a collective wage agreement—irrespective of whether the agreement is industry‐ or firm‐specific; see Guertzgen (2005). While aggregate firm‐level data provide a valuable data source for exploring the implications of collective bargaining coverage on rent‐sharing, the results are still subject to several limitations.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…In my own recent work, I use data from the IAB Establishment Panel and find wages to be positively related to establishment profits. However, this appears to be true only for uncovered establishments, since I fail to detect any positive relationship between wages and local profitability conditions in plants that are subject to a collective wage agreement—irrespective of whether the agreement is industry‐ or firm‐specific; see Guertzgen (2005). While aggregate firm‐level data provide a valuable data source for exploring the implications of collective bargaining coverage on rent‐sharing, the results are still subject to several limitations.…”
Section: Introductionmentioning
confidence: 85%
“…For example, one might suspect that, if centralised contracts shelter firms against excessive rent‐sharing at the firm level, highly profitable firms might systematically select themselves into the centralised regime. In an earlier paper based on the establishment‐level data (Guertzgen, 2005), I have demonstrated that the overall pattern of rent‐sharing across the three regimes is robust to the endogeneity of the bargaining regime.…”
mentioning
confidence: 94%
“…This approach is comparable to Gürtzgen () for collective bargaining coverage and Jirjahn () for works council existence. Yet, Table A3 shows that both variables are significant determinants of wages and productivity.…”
mentioning
confidence: 84%
“…Further, econometric research suggests that wages are higher under works councils (e.g. Addison, Teixeira, and Zwick, 2010;Gürtzgen, 2010). In short, the separation of distribution from production issues in the German system is inevitably partial.…”
Section: Erosionmentioning
confidence: 99%